2002
DOI: 10.1089/10872910260351276
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Services in the Boston HAPPENS Program: Human Immunodeficiency Virus-Positive, Homeless, and At-Risk Youth Can Access Services

Abstract: This study evaluates the factors associated with initiation of services in the Boston HAPPENS Program, which is a collaborative network of care consisting of multiservice outreach agencies, community health centers and hospitals, for human immunodeficiency virus (HIV)-positive and hard to reach youth who are 12-24 years old. The program served 2116 youth who were 19.8 +/- 2.9 years old; 64% female; 45% youth of color; 16% gay/lesbian, bisexual, or undecided; and 10% homeless or runaway. At first contact with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…The disparity between the rates of HIV among homeless youth and youth in the general population is significant given that .2-.4% of adolescents in the general population test positive for HIV (Rotheram-Borus et al 2003), highlighting the need for risk reduction methods developed for homeless youth. Homeless youth are difficult to connect to care and the need for intervention is high (Ensign and Bell 2004;Rotheram-Borus et al 2003;Woods et al 2002). The current study examined HIV risk behaviors and an integrated intervention targeted at reducing these behaviors in a sample of homeless youth between the ages of 14 and 22.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The disparity between the rates of HIV among homeless youth and youth in the general population is significant given that .2-.4% of adolescents in the general population test positive for HIV (Rotheram-Borus et al 2003), highlighting the need for risk reduction methods developed for homeless youth. Homeless youth are difficult to connect to care and the need for intervention is high (Ensign and Bell 2004;Rotheram-Borus et al 2003;Woods et al 2002). The current study examined HIV risk behaviors and an integrated intervention targeted at reducing these behaviors in a sample of homeless youth between the ages of 14 and 22.…”
Section: Introductionmentioning
confidence: 95%
“…Two studies report that between 10.2% and 11.5% of their sample of homeless youth (between the ages of 12 and 24) was positive for HIV (Pfeiffer and Oliver 1997;Woods et al 2002). The disparity between the rates of HIV among homeless youth and youth in the general population is significant given that .2-.4% of adolescents in the general population test positive for HIV (Rotheram-Borus et al 2003), highlighting the need for risk reduction methods developed for homeless youth.…”
Section: Introductionmentioning
confidence: 99%
“…41 Case management has been shown to influence positively the proportion of HIV-positive persons who receive medical care, 31 underserved youths' access to HIV medical care, 42 and infected persons' use of communitybased support services. 43 Persons who used crack cocaine, compared with persons who did not, reported that they were not given enough time.…”
Section: Perceptions Of Hiv Testing Servicesmentioning
confidence: 99%
“…Complicating these adverse health outcomes is the fact that many homeless youth are alienated from health and social services (Wright 1990b;Woods et al 2002). De Rosa et al (1999) found that only 28 percent of street youth reported ever accessing medical care services, 10 percent accessed substance abuse treatment services, and 9 percent accessed mental health services.…”
mentioning
confidence: 99%